2013
DOI: 10.5897/jidi2013.0117
|View full text |Cite
|
Sign up to set email alerts
|

HIV co-infection among tuberculosis patients in Dabat, northwest Ethiopia

Abstract: The aim of this study was to determine the prevalence of HIV co-infection among TB patients in Dabat district, northwest Ethiopia. Medical records of 1086 pulmonary and extrapulmonary tuberculosis patients registered from 2009 to 2012 at two health centers in the district were reviewed. HIV status was determined on 849 (78.2%) patients. The prevalence of HIV co-infection was 97 (11.4%). The majority, 61 (62.9%) and 90 (92.8%) of them were females and belonged to socio-economically productive age group, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 15 publications
6
17
1
Order By: Relevance
“…The socio-demographic variables of the TB/HIV patients in our study are similar to those of other researchers within and outside Nigerian state 26,28,29 . Although, majority of the TB patients were males, most of the TB/HIV co-infected were females.…”
Section: -27supporting
confidence: 86%
See 1 more Smart Citation
“…The socio-demographic variables of the TB/HIV patients in our study are similar to those of other researchers within and outside Nigerian state 26,28,29 . Although, majority of the TB patients were males, most of the TB/HIV co-infected were females.…”
Section: -27supporting
confidence: 86%
“…This finding is also similar to studies carried out in Dabat, Ethiopia, Malawi, Cameroonian district hospital and Rwanda. 19,20,28,30 .…”
Section: -27mentioning
confidence: 99%
“…Elsewhere, Akpaka et al [19] reported 11.6% TB and HIV co-infection in Jamaica. Also, 11.4% was found in Northwest Ethiopia [20], 55.5% in Western Kenya [9], 39.0% in Brazil [21] and 8.6% in India [22]. The fairly high prevalence of tuberculosis disease among HIV/AIDS patients seeking care and treatment in the selected health facilities in this research suggests a strong association between TB and HIV infection as posited by Tadesse and Tadesse [20].…”
Section: Discussionmentioning
confidence: 92%
“…Also, 11.4% was found in Northwest Ethiopia [20], 55.5% in Western Kenya [9], 39.0% in Brazil [21] and 8.6% in India [22]. The fairly high prevalence of tuberculosis disease among HIV/AIDS patients seeking care and treatment in the selected health facilities in this research suggests a strong association between TB and HIV infection as posited by Tadesse and Tadesse [20]. This study did not consider whether or not the HIV patients were already on Anti-Retroviral therapy, which may explain why the percentage of TB and HIV co-infection is higher than most of the other figures within Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Of 96245 TB patients tested for HIV infection, 9819(10%) were positive. Nevertheless, rate of co-infection among TB patients varies according to geographical location and people (Alemie and Gebreselassie 2014, Datiko et al, 2008, Tadesse and Tadesse, 2013.…”
Section: Original Researchmentioning
confidence: 99%